Is Religion Killing Us? : Violence in the Bible and the Quran. - Nelson-Pallmeyer, Jack (Bloomsbury Publishing PLC, 2015)
In this courageous and controversial book, Nelson-Pallmeyer explores the relationship between human violence and the scared texts of Jews, Christians, and Muslims.